Comparison between rocking analysis and kinematic analysis for the dynamic out-of-plane behavior of masonry walls - Giresini, Linda (2015)
This paper provides a contribution to the rocking analysis of masonry walls by making a comparison with the kinematic analysis suggested by the Italian code. It is shown that the latter approach is generally over-conservative and therefore potentially inappropriate for historic buildings, where rehabilitation can be expensive and can affect their cultural value. The equation of motion given by the Housner formulation, corresponding to the movement of a rigid block, is here modified to account for different boundary conditions at different heights of the wall. These boundary conditions, or horizontal restrainers, can represent vaults, transverse walls or retrofitting devices such as steel tie-rods. A systemic analysis of walls having different dimensions and slenderness is performed, and the results from the Italian code and rocking analysis are compared. Finally, the improvement in the response offered by retrofitting devices is discussed in terms of reduction of amplitude ratio.